Association between wet-bulb globe temperature with peptic ulcer disease in different geographic regions in a large Taiwanese population study - Yuh-Ching Gau; Chia-Yu Kuo; Wei-Yu Su; Wan-Ling Tsai; Ying-Jhen Wu; Ping-Hsun Wu; Ming-Yen Lin; Chih-Da Wu; Chao-Hung Kuo; Szu-Chia Chen (BMC Gastroenterology)
Abstract Background Peptic ulcer disease (PUD) is a common and important cause of morbidity worldwide, with a large impact on healthcare costs. Little research has been conducted on the association between wet-bulb globe temperature (WBGT) and PUD. The aim of this study was to explore this association among different geographical regions of Taiwan in a large sample of participants. Methods This is a cross-sectional study. The study participants (n = 120,424) were enrolled from the Taiwan Biobank (TWB) and resided across northern, central, southern and eastern Taiwan. Self-reported questionnaires were used to ascertain the occurrence of PUD. Average WBGT values were recorded during working hours (8:00 AM to 5:00 PM) and the noon period (11:00 AM to 2:00 PM) for each participant at 1, 3, and 5 years before the TWB survey year. The association between WBGT and PUD was examined with logistic regression analysis. Results The 1-year and 5-year noon WBGT values per 1℃ increase were significantly associated with a low prevalence of PUD in northern Taiwan (odds ratio [OR], 0.960, 95% confidence interval [CI], 0.925–0.955; OR, 0.962, 95% CI, 0.929–0.997; respectively). In contrast, there were no significant associations between WBGT and PUD in central Taiwan. In southern Taiwan, the 1-, 3-, and 5-year WBGT values per 1℃ increase during the noon period (OR, 0.875, 95% CI, 0.873–0.909; OR, 0.860, 95% CI, 0.825–0.896; OR, 0.848, 95% CI, 0.812–0.885; respectively) and working period (OR, 0.852, 95% CI, 0.825–0.880; OR, 0.845, 95% CI, 0.816–0.876; OR, 0.832, 95% CI, 0.0.801–0.863; respectively) were significantly associated with a low prevalence of PUD. However, in eastern Taiwan, the 1-, 3-, and 5-year WBGT values per 1℃ increase during the noon period (OR, 1.074, 95% CI, 1.022–1.127; OR, 1.058, 95% CI, 1.013–1.104; OR, 1.058, 95% CI, 1.013–1.105; respectively), and the 3- and 5-year WBGT values per 1℃ increase during the working period were significantly associated with a high prevalence of PUD (OR, 1.049, 95% CI, 1.003–1.097; OR, 1.047, 95% CI, 1.001–1.095; respectively). Based on nonlinear trend analysis, WBGT was categorized into three groups for the noon period or work period, and the results were similar to and generally consistent with those in linear models. Conclusion The associations between WBGT and PUD differed across the geographical regions of Taiwan. In northern and southern Taiwan, increases in average WBGT values were significantly associated with a low prevalence of PUD. In addition, this relationship was much stronger in southern Taiwan than in northern Taiwan. Of note, there was a reverse relationship between WBGT and PUD during the noon and working periods in eastern Taiwan. Further studies are needed to elucidate the effects of WBGT on PUD.